Review of ant genus Pachycondyla Smith, 1858 in Brazil (Hymenoptera: Formicidae) - Marcineiro, Frederico S. R.; Lattke, John E. (Zootaxa, 2024)
We review the taxonomy of the Neotropical species of the genus Pachycondyla. A new species (Pachycondyla beneditoi sp. n.) is described. Ponera pilosa new syn. is synonymized with P. crassinoda, based on a type male. Pachycondyla fuscoatra is redescribed and its distinctness from P. impressa is discussed. Pachycondyla harpax is still a taxonomic problem, with much morphological variation over a wide distribution. Pachycondyla impressa does not occur in Brazil; all previous records are P. fuscoatra or P. beneditoi. The gyne of P. lenkoi is described. Pachycondyla constricticeps new syn. is synonymized with P. striata. A neotype for P. fuscoatra is designated and lectotypes for P. harpax, P. impressa and P. striata are designated. An identification key for the Neotropical species is presented.